Eficiência de fungos entomopatogênicos no controle do percevejo-bronzeado-do-eucalipto (Thaumastocoris peregrinus) (Hemiptera: Thaumastocoridae) em condições de campo - Rocha Junior, Valter Ferreira (2017)
Brazil is the world's leader in productivity of Eucalyptus plantations, with approximately 6 million hectares of planted area and optimistic expansion projections in the coming years. Native to Oceania, the species was introduced to Brazil, and its production has been supported by the development of silvicultural and breeding techniques and a wide genetic base for clonal production. However, poor phytosanitary measures have led to the occurrence of exotic pests, which are potentiated by the absence of specific natural enemies and plantation homogeneity. This fact increases the cost with forest protection and directly interferes with the country's competitiveness in foreign markets. Thaumastocoris peregrinus is a key-pest in Eucalyptus plantations,that occurs worldwide, being detected in Brazil in 2008. The pest feeds on the sap of leaves, resulting in chlorosis, followed by tanning; in severe infestations, the damage can lead to leaf abscission and plant death. Chemical control (Bifenthrin) is used in emergency cases. However, environmental certification systems do not recommend this practice due to the high toxicity to humans and the environment. Therefore, alternative control strategies have been studied, such as biological control, which is potentially less toxic and is in compliance with the social and environmental aspects of forest plantations, according to environmental certification systems. Microbial control has been extensively and successfully studied in the country, such as entomopathogenic fungi, and thus, this procedure has been considered as a potential alternative to combat Thaumastocoris peregrinus. The first pathogens associated with insects control can be found naturally or isolated, or can be massively produced and stored for use in the field. Due to the possibility of being isolated and massively produced, a market for entomopathogenic fungi has been created, which enabled the development of mycoinseticide products. The fungi Beauveria bassiana, Metarhizium anisopliae, Isaria fumosorosea and Beauveria brongniartii have been used in this industry. The present study aimed to evaluate the efficiency of microbial control applied to T. Peregrinus in field conditions as a viable alternative to be inserted in the integrated management of this pest. The most effective treatment is the chemical control (Bifenthrin), followed by the biological control with I. fumosorosea, B. bassiana, and Metarril®. The entomopathogenic fungi I. fumosorosea and B. bassiana proved to be potential alternatives for biological control in the Integrated Management of T. peregrinus.